A Mathematical Programming for an Employees Creativity Matrix Cubic Space Clustering in Organizations - Fazlollahtabar, Hamed (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
Here, we investigate different structural aspects teams’ network organization and their creativity within a knowledge development program (KDP). Initially, a pilot group of employees in an organization is selected. This group is evaluated through creativity parameters using a questionnaire. Considering the questionnaires’ data, a creativity matrix is configured by a binary scoring. Applying the creativity matrix, clustering is performed via mathematical programming. The pilot group is divided into some research teams. The research subjects are submitted to the teams. Finally, an allocated problem is solved and some new research subjects are evolved to be assigned to the next configured teams. This procedure is repeated dynamically for different time periods.